Associations of Facial Proportionality, Attractiveness, and Character Traits. Issue 5 (27th July 2022) - Villavisanis, Dillan F.; Workman, Clifford I.; Cho, Daniel Y.; Zapatero, Zachary D.; Wagner, Connor S.; Blum, Jessica D.; Bartlett, Scott P.; Swanson, Jordan W.; Chatterjee, Anjan; Taylor, Jesse A.
Abstract : Background: Facial proportionality and symmetry are positively associated with perceived levels of facial attractiveness. Objective: The aims of this study were to confirm and extend the association of proportionality with perceived levels of attractiveness and character traits and determine differences in attractiveness and character ratings between "anomalous" and "typical" faces using a large dataset. Methods: Ratings of 597 unique individuals from the Chicago Face Database were used. A formula was developed as a proxy of relative horizontal proportionality, where a proportionality score of "0" indicated perfect proportionality and more negative scores indicated less proportionality. Faces were categorized as "anomalous" or "typical" by 2 independent reviewers based on physical features. Results: Across the ratings for all faces, Spearman correlations revealed greater proportionality was associated with attractiveness ( ρ = 0.292, P < 0.001) and trustworthiness ( ρ = 0.193, P < 0.001), while lesser proportionality was associated with impressions of anger (ρ = 0.132, P = 0.001), dominance (ρ = 0.259, P < 0.001), and threateningness ( ρ = 0.234, P < 0.001). Mann-Whitney U tests revealed the typical cohort had significantly higher levels of proportionality (–13.98 versus –15.14, P = 0.030) and ratings of attractiveness (3.39 versus 2.99, P < 0.001) and trustworthiness (3.48 versus 3.35, P < 0.001). Conclusions: This study demonstrated that facial proportionality is not only significantly associated with higher ratings of attractiveness, but also associated with judgements of trustworthiness. Proportionality plays a role in evoking negative attributions of personality characteristics to people with facial anomalies.